Haemoglobin Increment by Red Blood Cells Transfusion in Cancer Patients With Anaemia (Journal of Chittagong Medical College Teachers' Association, 2014)
Severe anaemia is usually treated with red blood cell (RBC) transfusion and in some cases moderate anaemia also requires transfusion. Traditionally one unit of red blood cells is transfused to increase the hemoglobin (Hb) level by 1 gm/dl, although no consensus guideline is available in our country. This study was done to see how much hemoglobin level was increased after transfusion of one unit of red blood cells in cancer patients with anaemia in our people. During the period of July 2012 to December 2012, 160 patients were studied in the Department of Transfusion Medicine of National Institute of Cancer Research and Hospital (NICRH), Mohakhali, Dhaka. All patients were aged >18 years of both sexes having a haemoglobin level of